Plant Anatomy - Crang†, Richard; Lyons-Sobaski, Sheila; Wise, Robert (Springer, 2019)
The science of plant anatomy extends back to the late seventeenth century and, by now, spans over 300 years and encompasses hundreds of thousands of reports in the scientific literature. The early plant anatomy research was summarized in 1899 by Dr. Hans Solereder in his two volume work entitled Systematische Anatomie der Dicotyledonen: Ein Handbuch für Laboratorien der wissenschaftlichen und angewandten Botanik. The 1908 English translation by Boodle, Fritsch, and Scott remains as fresh, informative, and useful today as when it was published over 100 years ago. Several important texts were published in the 1950s. The two-volume work of Metcalfe and Chalk, Anatomy of the Dicotyledons (1950) with second editions in 1979 (Volume 1) and 1983 (Volume 2), is a thorough survey of anatomical traits and features arranged by family. Some of the taxonomy has been rearranged, but the anatomical references remain accurate and valuable. The year 1953 saw the publication of the first edition of the classic Plant Anatomy by Katherine Esau. Encyclopedic in its coverage, insightful in interpretation, and complete in its synthesis, “Esau” (as it has been referred to by several generations of botanists) remains a go-to reference to this day. A second edition was released in 1977 and Dr. Ray Evert authored the third, revised edition, published in 2006. Additionally, the 1988 Plant Anatomy by Dr. James Mauseth and Dr. Avraham Fahn’s 1967 Plant Anatomy (4th edition in 1990) belong on every plant anatomist’s book shelf as valuable references.
A Concept-Based Approach to the Structure of Seed Plants